Analisis Efektifitas UI/UX Design Software Pengolah Gambar Menggunakan Metode Design Thingking terhadap Kenyamanan Pengguna dalam Industry Animasi - M. Fakhri Sholahuddin; Tata Sutabri (Router : Jurnal Teknik Informatika dan Terapan, 2024)
In the animation industry, the effectiveness of user interface (UI) and user experience (UX) design in image processing software is crucial for enhancing user comfort and productivity. This study aims to evaluate the UI/UX design in software belonging to the Adobe family, such as Photoshop, Illustrator, and After Effects. The employed methodology is Design Thinking, which includes the steps of Empathize, Define, Ideate, Prototype, and Test, to analyze each aspect of UI/UX design. Data were gathered through surveys and interviews with industry professionals to understand their experiences and perspectives. Preliminary results indicate that while Adobe applications are generally satisfactory, some software like After Effects and Illustrator require specific adjustments to the workspace menu to better meet user needs. These findings highlight areas needing improvement in image processing software to enhance user comfort and work efficiency. This research is expected to contribute to the development of more user-centered software, thereby improving user experience quality in the animation.